The Structure, Populations, and Kinematics of the Milky Way Central and Inner Bulge with OGLE, APOGEE, and Gaia Data - Xiao Han; Hai-Feng Wang; Giovanni Carraro; Martín López-Corredoira; Yuan-Sen Ting; Yang-Ping Luo; Guan-Yu Wang; (MWLUDPSG Collaboration) (The Astrophysical Journal)
We present an analysis of the structure, kinematics, and chemo-dynamical properties of the Milky Way bulge using RR Lyrae stars from Optical Gravitational Lensing Experiment (OGLE), and giant stars from APOGEE and Gaia that have distances placing them in the inner Galaxy. First, using a sample of 1879 ab-type RR Lyrae stars (RRabs) from OGLE-IV, we identified three populations: central bulge RRabs, the inner bulge RRabs, and halo or disk interlopers, based on their apocenters derived from orbital integration. Inner bulge RRabs kinematically align with the Galactic bar, while central bulge RRabs show slower rotation with lower velocity dispersion. Higher velocity dispersion stars were identified as halo/disk interlopers. Then, an orbital analysis of 28,188 APOGEE Red Clump and Red Giant Branch stars revealed kinematic properties consistent with RRabs, and the chemical abundance distribution displayed a bimodal stellar density pattern, suggesting complex star evolution histories and slightly different star formation histories for the inner bulge and central bulge. The differences in the density distribution on the ∣ Z ∣ _max -eccentricity plane for the central bulge, inner bulge, and interlopers are clearly detected. It is found that the classification of bulge stars based on orbital parameters, rather than solely on metallicity, provides a more accurate population separation. As the inner bulge, which contains the highest fraction of stars, traces the bar formed by the instability of the Galactic disk, our results support that the pseudobulge is the primary origin of the bulge. Furthermore, fitting the observed data to both the boxy and X-shaped bulge models indicated a preference for the boxy bulge.